Rancangan Projek InSPIRE* Darjah (1-3) Dan Pengaruhnya Ke Atas Prestasi Murid-Murid Di Dalam Penilaian Darjah 5 (1985) - A Lourdusamy, A Lourdusamy; R. Santhiram, R. Santhiram (Penerbit Universiti Sains Malaysia, 1987)
Improving the quality of education is possibly the greatest educational challenge faced by developing countries. Thus. with financial support from IDRC (Canada) and manpower resources from the Ministry of Education, a group of educationists based at the Universiti Sains Malaysia in 1977, embarked on a Research and Development project to test out an iintegrated strategy of programmed instruction to improve the quality of rural primary education. Although the project's work was overtaken by drastic reform of the national educational system. this paper examines whether the first three years of InSpire programme (from Std. 1 - 3) had any lasting carry-over effect which could be evaluated through the Std. 5 National Assessment Examination.